Do Price Discreteness and Transactions Costs Affect Stock Returns? Comparing Ex‐Dividend Pricing before and after Decimalization - Graham, John R.; Michaely, Roni; Roberts, Michael R. (Journal of Finance, 2003)
Abstract By the end of January 2001, all NYSE stocks had converted their price quotations from 1/8s and 1/16s to decimals. This study examines the effect of this change in price quotations on ex‐dividend day activity. We find that abnormal ex‐dividend day returns increase in the 1/16 and decimal pricing eras, relative to the 1/8 era, which is inconsistent with microstructure explanations of ex‐day price movements. We also find that abnormal returns increase in conjunction with a May 1997 reduction in the capital gains tax rate, as they should if relative taxation of dividends and capital gains affects ex‐day pricing.